A ten-year review of neonatal bloodstream infections in a tertiary private hospital in Kenya - Kohli-Kochhar, Ruchika; Omuse, Geoffrey; Revathi, Gunturu (The Journal of Infection in Developing Countries, 2011)
Introduction: Neonatal mortality in developing countries is usually due to an infectious cause. The gold standard of investigation in developing countries is a positive blood culture. It is important to know the aetiology of neonatal bloodstream infections so that empiric treatment can be effective. Methodology: We conducted a retrospective clinical audit over ten years between January 2000 until December 2009, looking at the aetiology of both early and late onset neonatal sepsis. We analysed data from 152 (23%) patient isolates out of 662 suspected cases of neonatal sepsis. Results: Our study revealed that Gram-positive organisms were the predominant cause of both early and late onset sepsis; the common isolates were Staphylococcus epidermidis (34%) and Staphylococcus aureus (27%). There were no isolates of group B Streptococcus. Candida species was isolated only in patients with late onset sepsis (6.9%). Bacterial isolates were relatively sensitive to the commonly used first- and second-line empiric antibiotics. Conclusion: Gram-positive organisms remain the major cause of neonatal bloodstream infections in our setup. The findings of this study will guide clinicians in prescribing the right empiric therapy in cases of suspected neonatal sepsis before the definitive culture results are obtained.